Hydroa vacciniforme-like lymphoma with systemic symptoms: Two case reports - Litao Wang; Yuwen Su; Jianzhong Zhang; Haiquan Wen; Guiying Zhang (Wolters Kluwer Medknow Publications, 2019)
Two Chinese children presented with relapsing papules, vesicles, ulcers on the face and limbs with systemic symptoms being caused by mosquito bite. Lesion biopsy revealed atypical lymphocyte in the dermis and subcutis. Immunohistochemistry identified cells as positive for CD3, CD45RO, TIA-1 and EBER. Taken together, both the patients were diagnosed with hydroa vacciniforme-like lymphoma. Two patients showed significant improvement in clinical symptoms after being treated with acyclovir, low dose predisone and IFN-α.